Discal cyst, a physical risk: a case report on endoscopic resection - Tan, Eng Kee; Harun, Mohd Hezery; Mohd Nasir, Noor'Ain; Mohamed Ramlee, Fadzrul Abbas; Lim, Teck Siang; Mohd Nasir, Mohd Nizlan (Springer, 2022)
Discal cysts are a rare diagnosis involving the formation of an intraspinal extradural cyst. They are a diagnostic challenge as it is difficult to differentiate discal cysts from other causes of back pain, neurological deficit, and radiculopathy. Due to its rarity, there is a lack of research-based evidence on the optimal management of the discal cyst. This case report aims to increase awareness of this diagnosis and to highlight a possible treatment option for this condition.